[Grinnell Arctic Expedition] - Grinnell, Henry, 1799-1874 (1854)
Manuscript map showing region around Grinnell Land and De Haven Bay in Canadian Arctic Archipelago. Relief shown by hachures. Manuscript map drawn with watercolor. Map listed in: Manuscript and annotated maps in the American Geographical Society Library: a cartobibliography, 2010. Color 1:500,000